Risk Management in Loan Programming of Public Works Infrastructure Construction (Lesson Learned of Indonesia Tourism Development Project) - Aryawidia Pariantho (Jurnal Indonesia Sosial Sains, 2026)
Loan programs serve as an alternative funding source for public infrastructure development in Indonesia, yet they often face significant delays due to complex organizational structures, readiness criteria, procurement procedures, and technical challenges. This study aims to formulate risk management recommendations for loan-funded public works infrastructure projects by drawing lessons from the Indonesia Tourism Development Project (ITDP), implemented from 2018–2024. The research adopts a qualitative case study approach using the Last Planner System (LPS) framework, which includes Master Schedule, Phase Planning, Modified Lookahead Planning, and Weekly Work Planning. Data were collected from CPMU, PMU, and PIU progress reports, operational manuals, audit records, and lender evaluation documents. The findings reveal that combining planning and construction within the same loan period is a primary source of delay, as the formulation of the Integrated Tourism Master Plan consumed nearly half of the project timeline. Other critical issues include land availability, procurement document mismatches, technical adjustments during construction, and institutional gaps in asset handover to local governments. The study concludes that loan programs should separate planning from construction phases, prioritize subprojects based on societal impact, ensure readiness criteria are fulfilled before commencement, and establish early stakeholder collaboration. These LPS-based recommendations provide a structured approach for future loan managers to anticipate and mitigate implementation delays.